From the Histological Model to the Mutational Model: The Study of Heavy Metals and Other Substances in New Antineoplastic Therapies (Global Journal of Medical Research, 2023)
The study of genetic mutations in tumours changes the therapeutic approach; in fact, we move into a different advanced and strategic phase by entering personalized precision medicine and shifting the focus from the tissue study of the tumour to the modification and proliferation of neoplastic cells. The therapeutic programs, especially in oncology, are changing. We are in a phase of transition from the histological model to the model of genetic mutation (mutation). When a person's immune defences do not respond to a disease it is because the body cannot produce or activate specific lymphocytes and antibodies against that disease. This causes of a lack of therapeutic response or recurrence of the disease.
Keywords: tumour disease; therapeutic response; complications; genomic modification; genomic and genetic tests